DIGITASI KAWASAN PERMUKIMAN KUMUH KECAMATAN ABELI KOTA KENDARI - Husain, Fajerullah Akbar; Ngii, Edward; Adzikin, Muhammad Thahir (Pascasarjana Universitas Halu Oleo, 2022)
Uncontrolled population growth, especially in urban areas, has a negative impact on social problems, one of which is the emergence of enclaves. Development and increasing population growth rates always bring changes, one of which is a change in the level of environmental quality. Rapidly growing population growth has implications for increasing space requirements for shelter and other facilities.The quality of the rapidly changing housing environment is encouraging managers and policy makers in the city to carry out monitoring and evaluation. The problem then is that measurement and evaluation require high costs, a lot of energy, and a relatively long time, given the very crowded and bustling city environment. Therefore we need a method that is able to overcome these obstacles.Characteristics of average slum in terms of indicators of building presentation, environmental accessibility, environmental drainage, drinking water services, water and sewage management, abeli village 15%, anggalomelai village 46%, continental nirae village 40%, bungkutoko village 52.80%, lapulu 27 %, pudai 65.62% and talia 32% and based on the slum table of abeli 15% are declared not slum, anggalomelai kelurahan 46% moderate slum, continental nirae village 40% mild slum, bungkutoko kelurahan 52.80% moderate slum, 27% mild slum kelurahan , pudai 65.62% moderate slums and 32% mild talia kelurahanEstablishment of a geographic information system based on the location map of the slum of Abeli sub-district. The geographic information system can display information and location of Abeli sub-district slum with five indicators namely buildings, environmental accessibility, environmental drainage, water service play and wastewater management which are spread in the Abeli sub-district and the establishment of a map-based geographic information system that can be utilized to search slum based on the area can be displayed on the map location Abeli district.keywords: slums, settlements, digitizing